2017
DOI: 10.1371/journal.pone.0184912
|View full text |Cite
|
Sign up to set email alerts
|

Degree sums and dense spanning trees

Abstract: Finding dense spanning trees (DST) in unweighted graphs is a variation of the well studied minimum spanning tree problem (MST). We utilize established mathematical properties of extremal structures with the minimum sum of distances between vertices to formulate some general conditions on the sum of vertex degrees. We analyze the performance of various combinations of these degree sum conditions in finding dense spanning subtrees and apply our approach to practical examples. After briefly describing our algorit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
2

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…Common generalizations of this optimization problem for the undirected and unweighted case include the dense, sparse, and minimum routing cost spanning tree problems. Many other variations of optimal spanning trees exist [15,16,[27][28][29][30][31][32][33][34][35][36], and such trees are relevant to an ever widening diversity of applications from optical network design [14,37] to networked oscillator synchronization [38].…”
Section: Introductionmentioning
confidence: 99%
“…Common generalizations of this optimization problem for the undirected and unweighted case include the dense, sparse, and minimum routing cost spanning tree problems. Many other variations of optimal spanning trees exist [15,16,[27][28][29][30][31][32][33][34][35][36], and such trees are relevant to an ever widening diversity of applications from optical network design [14,37] to networked oscillator synchronization [38].…”
Section: Introductionmentioning
confidence: 99%
“…Seeking the spanning tree of a given graph structure is a classic problem that has numerous applications and variations. For some examples of such study one may see [1,2,3,4,5,6,7,8,9]. In a weighted graph, finding the spanning tree with minimum total weight is known as the minimum spanning tree problem and is probably one of the most extensively studied problems.…”
Section: Introductionmentioning
confidence: 99%
“…Seeking the spanning tree of a given graph structure is a classic problem that has numerous applications and variations. For some examples of such study one may see [1][2][3][4][5][6][7][8][9]. In a weighted graph, finding the spanning tree with minimum total weight is known as the minimum spanning tree problem and is probably one of the most extensively studied problems.…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, minimizing a condition such as C j can be used to find a Sparse Spanning Tree (SST) in the given graph. In [9], through computational analysis, it was observed that for j = 4, 2, 0, 0 or 4, 2, 2, 0 or 4, 2, 2, 2 the corresponding objective functions…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation